TECHNOLOGICAL MODERNISATION PROSPECTS FORECAST OF THE MAIN INDUSTRIES IN RUSSIA BASED ON THE ASSESSMENT OF INNOVATIVE DEVELOPMENT LEVEL - Doroshenko, Yuri Anatolievich; Rudychev, Anatoliy Andreyevich; Riapukhina, Viktoriia Nikolayevna (Journal of Applied Engineering Science, 2021)
This article presents theoretical bases of organic modernization and tendencies of development of the main branches of industry in the economy of Russia. The prospects for the modernization of industry are assessed by the criteria for the dynamics of production and exports. The Kondratiev waves downward and upward are identified based on trends in these indicators. According to the Faltsman method, the forecast showed the growth and feasibility of modernizing crop farming, housing construction, and the automotive industry. But, does not show prerequisites for the growth of the oil industry and the military-industrial complex. The results of the study represent practical recommendations for industrial development strategies.